2015
DOI: 10.14814/phy2.12545
|View full text |Cite
|
Sign up to set email alerts
|

The effects of intragastric infusion of umami solutions on amygdalar and lateral hypothalamic neurons in rats

Abstract: Previous behavioral studies have suggested that l-glutamate, an umami substance, is detected in the gut, and that this information regarding glutamate is conveyed from the gut to the amygdala and the lateral hypothalamus (LH) through the vagus nerve to establish glutamate preference. In this study, we investigated the roles of the amygdala and LH in the information processing of gut glutamate. We recorded the activity of amygdalar and LH neurons during the intragastric administration of five test solutions (mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 65 publications
(136 reference statements)
1
3
0
Order By: Relevance
“…Uematsu et al (27) showed that rats that had a total abdominal vagotomy did not learn to prefer a flavor paired with intragastric MSG. Consistent with this observation, vagotomy also altered the neural response to intragastric MSG in the amygdala and lateral hypothalamus, which was taken as evidence that it blocked the coding of positive postingestive actions of glutamate (34). This contrasts with our findings that vagal surgical or chemical denervation does not block postoral carbohydrate or fat conditioning (35), which, in turn, is consistent with the lack of change in forebrain response to glucose after vagotomy (36).…”
Section: Flavor Preferences Conditioned By Intragastric Msgsupporting
confidence: 83%
“…Uematsu et al (27) showed that rats that had a total abdominal vagotomy did not learn to prefer a flavor paired with intragastric MSG. Consistent with this observation, vagotomy also altered the neural response to intragastric MSG in the amygdala and lateral hypothalamus, which was taken as evidence that it blocked the coding of positive postingestive actions of glutamate (34). This contrasts with our findings that vagal surgical or chemical denervation does not block postoral carbohydrate or fat conditioning (35), which, in turn, is consistent with the lack of change in forebrain response to glucose after vagotomy (36).…”
Section: Flavor Preferences Conditioned By Intragastric Msgsupporting
confidence: 83%
“…Surgical procedures have been described previously ( Matsumoto et al, 2012 ; Davaasuren et al, 2015 ). Briefly, rats were anesthetized with sodium pentobarbital (40 mg/kg; intraperitoneal, i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…Food exerts its reinforcing effects on the brain reward system via both gustatory (oral-sensory) and post-ingestive pathways ( Li et al, 2002 ; Jang et al, 2007 ; Margolskee et al, 2007 ; Dotson et al, 2010 ; Fernstrom et al, 2012 ). A previous neurophysiological study reported that intragastric (IG) infusion of amino acids changed neuronal activity in the lateral hypothalamus and amygdala ( Davaasuren et al, 2015 ). Furthermore, studies have suggested that hepato-portal glucose sensors, which act as an unconditioned stimulus for the acquisition of a learned-food-preference ( Delaere et al, 2013 ) and regulates several physiological functions such as glucose utilization ( Burcelin et al, 2000 ), may directly influence dopaminergic activity.…”
Section: Introductionmentioning
confidence: 99%
“…LHA glucokinase may also mediate glucoprivic feeding through direct connections between the LHA and the gut, as diet restriction induced neuronal activation of the LHA in mice ( 143 ). This brain-gut connection appears to occur via the vagus nerve and may be bidirectional, as vagotomy impaired LHA neuronal activation induced by intragastric infusions of various glutamate-containing solutions ( 38 , 171 ).…”
Section: Glucokinase and The Regulation Of Appetitementioning
confidence: 99%